Is Stem Cell a Curer or an Obstruction? - Siska Darmayanti; Rina Triana; Angliana Chouw; Nurrani Mustika Dewi (Molecular and Cellular Biomedical Sciences, 2017)
Stem cell research and therapy are progressing these days dramatically. Stem cell therapy holds enormous treatment potential for many diseases which currently have no or limited therapeutic options. Unfortunately, this potential also comes with side-effects. In this review, the positive and negative effects of regulation of stem cells will be explained. Stem cells are undifferentiated cells which able to develop into many different cells of types in the body during early life and growth. There are five types of stem cells: embryonic stem cells, induced pluripotent stem cells, somatic stem cells, fetal stem cells and mesenchymal stem cells. Stem cell transplantation is one form of stem cell therapy, it comes with different techniques sourced, and those are autologous and allogeneic transplantation stem cells. In an autologous transplant, a patient's blood-forming stem cells are collected, meanwhile, in an allogeneic transplant, target cells are replaced with new stem cells obtained from a donor or donated umbilical cord blood. Its abilities to maintain the phenotype, self-renewing and differentiate itself into specialized cells, give rise to stem cell as an innovation for the treatment of various diseases. In the clinical setting, stem cells are being explored for different conditions, such as in tissue repair and regeneration and autoimmune diseases therapy. But along with its benefit, stem cell therapy also holds some harm. It is known that the treatment using stem cell for curing and rehabilitation has the risk of tumor formation.Keywords: stem cell, therapy, transplantation, tumorigenic, mesenchymal stem cell, allogeneic